(untitled) (Applied Biological Research, 2023)
Staphylococci, involved in many human diseases, are present on human and animal body surfaces as well as in air, food and water. The general classification of staphylococci divides them in two major groups; coagulase positive and negative staphylococci. Coagulase-negative staphylococci (CoNS) are present as a part of normal skin andmucous membrane flora in humans. CoNS have long been considered as non-pathogenic organism but now they are considered pathogenic involved in infections related to prosthetic materials particularly in surgicalwounds. Virulence factors in CoNS are not very clearly established. Staphylococcus epidermidis is evolving as a resistant and powerful microbe related to nosocomial infections. Characteristics like biofilm formation, drug resistance and evolution of genetic variables contribute to its pathogenicity. This review elaborates the evidence of involvement of CoNS in various clinically important infections from recent and past literature.